2017
DOI: 10.1210/js.2017-00040
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Diabetes-Predisposing Variants in MODY Genes Among Danish Women With Gestational Diabetes Mellitus

Abstract: Context:Gestational diabetes mellitus (GDM), defined as any degree of glucose intolerance with first recognition during pregnancy, is a heterogeneous form of diabetes characterized by various degrees of β-cell dysfunction.Objectives:We aimed to estimate the prevalence of possibly pathogenic variants in the maturity-onset diabetes of the young genes GCK, HNF1A, HNF4A, HNF1B, and INS among women with GDM. Furthermore, we examined the glucose tolerance status in variant carriers vs noncarriers at follow-up.Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
(45 reference statements)
0
24
0
2
Order By: Relevance
“…Their knowledge regarding the social and family history of the patient can facilitate transferring from insulin to sulphonylureas, thus promoting better quality of life in different ways. [37,38] • Patients taking insulin for years may experience uncertainty, fear, anxiety and excitement on changing to tablets. • Changing from a routine of 2-4 insulin injections a day to tablet therapy improves lifestyle and self-image.…”
Section: Implications For Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Their knowledge regarding the social and family history of the patient can facilitate transferring from insulin to sulphonylureas, thus promoting better quality of life in different ways. [37,38] • Patients taking insulin for years may experience uncertainty, fear, anxiety and excitement on changing to tablets. • Changing from a routine of 2-4 insulin injections a day to tablet therapy improves lifestyle and self-image.…”
Section: Implications For Quality Of Lifementioning
confidence: 99%
“…Gjesing et al diagnosed 5-6% of women with GDM with GCK MODY. Furthermore, 6% of diet treated GDM Danish women were identified as having possibly pathogenic variants in GCK, HNF1A, HNF4A, HNF1B or INS [38]. These women are at high risk of developing diabetes after pregnancy, and the authors recommended that screening for mutations in these genes should be offered to women with GDM.…”
Section: Monogenic Diabetes and Pregnancymentioning
confidence: 99%
“…Gjesing et al 9 reported a combined GCK, HNF1A, HNF4A, HNF1B , and INS variant prevalence of 5.9% in Danish women with GDM. We calculated the minimum required sample sizeas 15 using OpenEpi software version 3.01, with 95% confidence level, 5% precision and 80% power.…”
Section: Methodsmentioning
confidence: 99%
“… 7 , 8 A recent study conducted in Denmark reported a 5.8% prevalence of variants of GCK, HNF1A, HNF4A, HNF1B , or INS among women diagnosed with GDM. 9 Heterozygous mutations in the GCK gene have also been reported to be a cause of a subtype of maturity-onset diabetes of the young (MODY), GCK-MODY or MODY 2. 10 Data on the link between GDM and GCK gene is scarce in the Indian perspective.…”
Section: Introductionmentioning
confidence: 99%
“…В исследовании Weng [6] в 1% случаев (n=66) выявлены мутации в гене HNF1A, а в работе Gjesing A. и соавт. мутации в генах HNF4A и HNF1A обнаружены в 3,7% случаев (13/354) [7]. До настоящего времени в отечественной литературе не описано течение диабета беременных, обусловленного мутациями в генах ядерных факторов гепатоцитов, в связи с чем мы приводим описание 7 клинических случаев неиммунного сахарного диабета типов MODY1 и MODY3.…”
unclassified